The study of the volatile fraction components from the plant material of «Lollo Rosso» lettuce species - Гуцол, Вікторія Володимирівна; Журавель, Ірина Олександрівна; Гур’єва, Ірина Геннадіївна (ScienceRise: Pharmaceutical Science, 2016)
Herbs are important source of biologically active compounds having different types of pharmacological activity. The attention is drawn both to herbs, traditionally used for prevention and treatment of different disorders, and to edible plants included in the every person’s daily diet. Lettuce, grown worldwide as leafy vegetables, is among them. Aim. The aim of our work was quantitative and qualitative determination of the volatile fractions components, obtained from leaves, roots and seeds of «Lollo rosso» lettuce species. Methods. Gas chromatography was used for quantitative and qualitative determination of the volatile fractions components of «Lollo rosso» lettuce species. Results. In result of research, in the volatile fraction of lettuce 31 compounds were identified and determined in leaves, 27 compounds were determined in roots, and 24 compounds were determined in seeds. Squalene was dominating substance in all types of the herbal material. Conclusion. Obtained results can be used for development of the Quality control methods for lettuce herbal material